Lucky breaks - Patron, Susan 1948- (Random House, Inc., 2009)
Lucky makes a new friend, gets stuck in a well, meets up with a wild burro, discards something she didn't know was precious, and discovers the secret of the universe in this charming and funny sequel to the Newbery Award-winning The higher power of lucky
Empfohlen für Kinder von 8 bis 12 Jahren
Keywords: Friendship / Juvenile fiction; Children's accidents / Juvenile fiction; Donkeys / Juvenile fiction; Friendship / Fiction; Accidents / Fiction; Donkeys / Fiction; Children's accidents; Donkeys; Friendship; Friendship -- Fiction; Interpersonal relations -- Fiction; Adoption -- Fiction; Abandoned children -- Fiction; Deserts -- Fiction; California -- Fiction; Hörbuch; Kinderbuch; CD